Water and Solute Distribution Pattern in Soil Under Point Source Trickle Irrigation - M. Ekhmaj, Ahmed I. (2005)
A basic requirement in the design of a trickle irrigation system is to obtain more information about the shape and size of the wetted soil zone. This will ensure precise placement of water and nutrients in the active root zone to meet the requirements of precision farming. A series of laboratory and field experiments were conducted to determine water and solute distribution pattern in soil under point source trickle irrigation. Three types of experiments were conducted. The focus of the first type of experiment was to study the effect of water application rate and the amount of water on water movement in the lateral and vertical direction. River sand and sandy loam soil were used as the media in a plexiglass container. These experiments were conducted under laboratory conditions where the application rates of 0.75 and 3.4 I/h were used for river sand soil while 1 and 3.0 I/h were used for sandy loam soil. The second type of experiments was conducted on river sand in the laboratory using a wooden box. The purpose of this experiment was to study the effect of application rate and amount of irrigation water on the surface wetted radius. Application rates of 3, 5.5 and 7 I/h were used. The third type of experiment was conducted under field conditions. The experiments were designed for field evaluation of water and solute movement from a point source. Sandy and sandy loam soils were selected for these experiments and the application rates varied from 1.5 to 6 Ilh. The results fiom the experiments revealed that for all soil types, lateral movement of the wetting front and the surface wetted radius as measured at the soil surface approached a limit with elapsed time. A linear relationship was found between vertical wetting front advance and the square root of elapsed time. The results obtained fiom both plexi glass and wooden box experiment showed that the water application rates caused a notable effect on the surface wetted radius, where increase in the application rates contributed to an increase in the surface wetted radius. On the other hand the statistical analysis of the field experiment results showed insignificant effect of the application rates on the surface wetted radius. Increase in the discharge rate caused a decrease in the vertical advance of the wetting front for both sandy and sandy loam soils under field conditions, and sandy loam soil in the plexiglass experiments. The maximum volumetric moisture content after irrigation was found in the region just below the irrigation source. The statistical analysis of moisture distribution data under field conditions showed insignificant effect of water application rate on the water content distribution within the boundary of 17.5 and 27.5 cm in radial and vertical distance, respectively. The patterns of the chloride concentration distribution were similar to those for moisture content distribution. The effect of inlet chloride concentration on the distribution of chloride concentration was significant in both soils. The greater the concentration at the inlet, the higher the chloride concentration in the soil. For both types of soil, most of the treatments indicated insignificant effect of application rate on the chloride distribution. Two simple models based on the average change in volumetric water content (AO), total volume of water applied (V,), application rate (q,) and the saturated hydraulic conductivity (ks) were developed to determine the surface wetted radius (r) and vertical advance of the wetting front (z) produced from point source trickle irrigation, r= 0.26 -0.03 -0 03 ~ 0 -V, ~ -q, ~ ~ ks . and z= 80-0.38 V, 0.36 q, -0.1k s0 .1 9 . These models were verified with the data from this study and other published experiments under different conditions. The results obtained from both types of data improved the capability of using these models for designing a trickle irrigation system. In this study, Hydrus-2D model was used to simulate water and solute distribution under point source trickle irrigation. Good agreements were found between simulated and experimental results regarding location of the wetting front, water distribution and solute concentration under different application rates.